Two Sides of the Coin: The Roles of Adverse Childhood Experiences and Positive Childhood Experiences in College Students’ Mental Health - Bhargav, Madhav (Journal of interpersonal violence, 2024)
Several studies have established a link between adverse childhood experiences (ACEs) and mental health issues in college students. However, less is known about how positive childhood experiences (PCEs) may promote mental health and well-being, and potentially act as a buffer in the relationship between risk exposure and poor outcomes. This study investigates how ACEs and PCEs relate to college students’ mental health (N = 321), within the framework of Resiliency Theory with specific attention focus on the compensatory and the protective factors models. Three key hypotheses were examined using quantitative data collected by way of an online anonymous survey: (1) ACEs will predict poorer mental health outcomes; (2) PCEs will predict better mental health outcomes and will lessen the negative effects of ACEs on mental health outcomes (compensatory factor model), and (3) PCEs will moderate the association between ACEs and mental health outcomes so that the relationship will be weaker among participants with higher PCEs (protective factor model). Findings supported each of these hypotheses and are important for our understanding of the long-term mental health correlates of ACEs and PCEs among college students. Our study underscores the importance of promoting PCEs while also underscoring the necessity of proactively preventing ACEs. Practical implications are discussed in relation to improving assessments of student needs and providing targeted interventions for those at risk.